A Case Report of Coronary-Subclavian Steal Syndrome Treated with Carotid to Axillary Artery Bypass. (20th July 2009) - Al-Jundi, Wissam; Saleh, Aiman; Lawrence, Kathryn; Choksy, Sohail
Abstract : Coronary-subclavian steal syndrome results from atherosclerotic disease of the proximal subclavian artery causing reversal of flow in an internal mammary artery used as conduit for coronary artery bypass. This rare complication of cardiac revascularisation leads to recurrence of myocardial ischaemia. When feasible, subclavian angioplasty and/or stent placement can provide acceptable result for these patients. Vascular reconstruction through carotid to subclavian artery bypass has been the standard procedure of choice. Other interventions in literature include axilloaxillary bypass and subclavian carotid transposition. This case report describes the use of carotid axillary artery bypass for the treatment of coronary-subclavian steal syndrome.